Microstructure and electrochemical corrosion behaviour of API 5L X90 pipeline steel in a simulated soil environment - Mahdi Yeganeh; Mostafa Eskandari; Hasan Mousavi (Journal of Electrochemical Science and Engineering)
API 5L X90 pipeline steel, valued for its high strength in oil and gas pipelines, is susceptible to corrosion in aggressive soil environments containing moisture, chlorides, and other corrosive agents. This study aims to investigate the electrochemical corrosion behaviour of this steel in a simulated soil solution to understand its corrosion mechanisms and pipeline durability. The research employs electrochemical techniques, including electrochemical impedance spectroscopy, electrochemical noise and potentiodynamic polarization testing. Microstructural analysis showed that the composition of the steel, consisting of elongated ferrite grains, polygonal ferrite, granular bainite, and small amounts of martensite-austenite (MA), significantly influences its corrosion behaviour. EIS results indicated the presence of multiple time constants due to various oxide films and corrosion products, which hindered the penetration of corrosive species over time. As a result of corrosion products forming on the active sites and rendering them inactive, the charge transfer resistance increased by approximately 1.5 times. Potentiodynamic polarization tests indicated an absence of passivation, accompanied by a decrease in corrosion current density and a shift in corrosion potential toward the cathodic direction during immersion. Surface analysis after 100 hours identified localized corrosion, including cracks and pits, which pose risks to the steel’s structural integrity. The findings emphasize the need to understand the corrosion processes and their impact on impedance characteristics, advocating for targeted corrosion prevention and treatment strategies to enhance pipeline longevity and reliability.